(3GdHGQY aj CMcGe GdfLhes - (3GdTjHGfj , Ydj Hf CHj GdQLGdj GdTjHGfj GdeZQHj GdbjQhGfj, CHh GdMSf,J (B432 (3g` s ((3HfOQ ShQJ s)
(3ChdgG (B:s
(3bGd Ydj GdMeO ddg GdhGMO GdbgGQ gPG cJGH LeYJ ajg eYGfj Yde GdfLhe hZQGFH CSQGQgG , hGNJQJg ef cKjQ ef cJH YdeGFgG hCVaJ Edjg eG acQJi , hCJJ Ydjg JLQHJi s
(3BNQgG (B:s
(3Ke jchf HYO Pdc bJGd TOjO Ch Ef CfbU ef GdMhJ aEf Gdedc hjchf SdGeI HbGFg hcKQI CeWGQg hGddg CYde HGdUhGH s
(3HgG fXGe GdJYbjHIs
(3HgG LOGhds
(3cJHJ Hbde Objb eged GdfbW bdjdkGs
(3JYGhf YdjgG fGSNGf s
(3bhHdJ HfOQ ShQJ SfI (B1121(3g` s
(3HChdgG Jedc SfI (B1194(3g` s
Keywords: (3Gdadcs